2019
DOI: 10.1108/ijoa-05-2017-1159
|View full text |Cite
|
Sign up to set email alerts
|

Progressive human resource management and firm performance

Abstract: Purpose This study aims to examine the adoption and efficacy level of progressive human resource management (HRM) practices in various organizations operating in India. Design/methodology/approach Primary data based on 615 respondents from 103 domestic firms and 116 foreign multinational corporations (MNCs) operating in India were gathered and analyzed using statistical techniques like t-test, confirmatory factor analysis and structural equation modeling. Findings The results reveal that the adoption of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…Over the years, numerous studies have demonstrated the positive effects of strategic human resource management (SHRM) on both employees' behaviour and organisational performance (Korff et al, 2017;Gahlawat and Kundu, 2019). In the literature, the influence of SHRM on employees' work attitude has gained further attention for both empirical (Korff et al, 2017;Salminen et al, 2017) and theoretical contributions (Delery and Roumpi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, numerous studies have demonstrated the positive effects of strategic human resource management (SHRM) on both employees' behaviour and organisational performance (Korff et al, 2017;Gahlawat and Kundu, 2019). In the literature, the influence of SHRM on employees' work attitude has gained further attention for both empirical (Korff et al, 2017;Salminen et al, 2017) and theoretical contributions (Delery and Roumpi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this heightened awareness over employees, the institutional structure in relation to human resource management (HRM) has uplifted considerably in India. Scholars (e.g., Gahlawat & Kundu, 2019; Som, 2008) have stated that Indian organizations are extensively embracing the Western-developed notions of HRM such as high-performance work systems (Appelbaum et al, 2000), high-involvement work systems (Guthrie, 2001) and innovative HRM (Boselie, 2011) in order to survive and compete in the highly globalized environment. These progressive HRM systems representing “bundles” of HR practices are often reported to have a positive influence on organizational effectiveness (Boon, Hartog, & Lepak, 2019 ; Boxall & Macky, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Conferring to the moderated mediation analysis, the results imply that the impact of business strategies on employees' ITL through HPWS do not vary in different types of firms, be it manufacturing, service, domestic or foreign MNC. It can be argued that recent contextual changes including rapid economic development and change in employees' work-related values, may have shaped an environment in India where organizations irrespective of their ownership type and nature are adopting advanced HRM systems like strategic HRM and HPWS to achieve competitive advantage (Sahu, 2018;Gahlawat and Kundu, 2019 are turned effective to an equitable extent regardless of the organizational context. Allinclusive, the current study provides some interesting results in relation to the validation of progressive HRM systems in Indian context.…”
Section: Discussionmentioning
confidence: 99%
“…However, local firms are argued to be still in the infant stage in application of HRM as is understood internationally (Warner, 2004). Other studies from India have also indicated that Indian firms are less formal and less structured in their approach to HRM (Budhwar and Sparrow, 1997;Gahlawat and Kundu, 2019) and copy their Western counterparts in formulating and implementing strategic HRM programmes and systems (Som, 2008). Additionally, Cooke and Saini (2010) established that Indian firms in an attempt to "catch up" with the MNCs adopt HR practices just to be seen as progressive, modern and innovative; they ignore examining the utility of these practices to the firm and their support to business strategy.…”
Section: Moderating Effects Of Nature and Ownership Forms Of The Firmsmentioning
confidence: 99%